Selection of Peanut Skin as a Growing Medium for Moon Orchid (Phalaenopsis amabilis) - Nur Rokhimah Hanik; Sri Harsono; Anwari Adi Nugroho (Universitas Mataram, 2020)
Ferns are a planting medium that is commonly used in Phalaenopsis cultivation, but the growing demand for fern will increase the selling price and the availability of fern is limited. So a solution is needed to reduce the maintenance and maintenance costs by utilizing peanut shells as a growth medium. The purpose of this study is: 1. To determine the effect of peanut skin media on the growth of Phalaenopsis amabilis month orchid 2. To find out better which influence between fern media, fern media plus peanut skins, or peanut skin media on orchid growth month of Phalaenopsis amabilis. When the research began in May 2019 until October 2019. The research object was in the form of a 4-5 month-old orchid, the research location in the Biology Laboratory of the Faculty of Veterinary Science, Bangun Nusantara University, Sukoharjo. Simple randomized study design with three treatments. Treatment A by giving fern media, treatment B by giving fern media mixed with peanut skin, and treatment C by giving peanut skin media. The research variables are the number of leaves, leaf length, leaf area, number of roots and root length measured once a week for 8 weeks. Data analysis with 2. Variance Test (Anova or Kruskal Wallis test) 3. Duncan Multiple Range Test (DMRT) or Moods Median Test. From the results of the study it was found that all observed growth variables (number of leaves, leaf width, leaf length, leaf area, number of roots, average root length, and wet weight) were treated with fern, mixed (Fern and peanut shell) media, and media of peanut skin, there was no significant difference in the effect on the growth of the month orchid. Which means that the three types of media both have an influence on the growth of Phalaenopsis amabilis month orchids. media ferns and peanut shells have their advantages and disadvantages of each. So it can be concluded that, 1. The use of peanut skin media can affect the growth of Phalaenopsis amabilis month orchids. 2. Media fern, a mixture of fern media and peanut skins, and peanut skin media can provide the same effect on the growth of Phalaenopsis amabilis month orchids. From the results of the study it can be recommended that peanut skins can be used as a medium or a mixture of growing media of Phalaenopsis amabilis orchids.